Conceptualizing the roles of psychological safety, caring management and inclusiveness in safety culture maturity in Malaysia’s oil and gas industry - Abdul Wahat, Nor Wahiza; Guan, Ng Yee; Mustaffa, Masfarita (Human Resource Management Academic Research Society (HRMARS), 2024)
The number of recent studies related to safety culture maturity in the context of oil and gas industry in Malaysia is rather limited, considering the fact that the oil and gas is a high-risk industry. A few existing studies on safety culture maturity in Malaysia were conducted in other context such as maritime. Thus, it leads to the research question of this study which is ‘what constitutes safety culture maturity in the context of oil and gas industry in Malaysia?’. This qualitative study was geared towards conceptualizing safety culture maturity in Malaysia’s oil and gas industry. It involved 9 informants from a project management team. Conducted focus group discussion and thematic analysis identified psychological safety, caring management and inclusiveness as significant domains of safety culture maturity. Technology-wise, this study implies that by leveraging technologies to facilitate better communication, organizations can create a mature safety culture, that protects, empower and lead to overall performance and well-being of employees.